Study guide to accompany Engineering mechanics. - Meriam, J. L. (John Wiley and Sons, 1997)
Definitions and principles. Units. Problem formulation. Analysis techniques. Rectilinear motion. Equations of motion. Work-energy. Impulse-momentum...